Understanding university students' experiences of sitting while studying at home: A qualitative study. - Hannah Clare Wood; Sanjana Prabhakar; Rebecca Upsher; Myanna Duncan; Eleanor J Dommett; Benjamin Gardner (PLoS ONE)
University students are typically highly sedentary, which is associated with adverse physical and mental health outcomes. Attempts to understand university students' sedentary behaviour have typically focused on on-campus teaching and learning activities. While such research has documented that students perceive studying as one of the main barriers to reducing sedentary behaviour, there is little understanding of how and why studying incurs sitting, especially during home-based studying. We investigated how students' experience sitting when studying at home. Fourteen UK undergraduates (10 female; mean age = 20 years) participated in semi-structured interviews that explored their experiences, beliefs, and attitudes regarding sitting while studying at home. Data were analysed using Reflexive Thematic Analysis. Four themes were constructed, focusing on knowledge and attitudes towards sitting, prioritisation of study tasks, sitting as an integral part of the study environment, and sitting as part of the optimal mental 'zone'. Whilst participants demonstrated awareness of the potential health risks associated with prolonged sitting they prioritised productivity when studying at home and believed that interrupting their sitting would compromise productivity, making home-based studying particularly conducive to sedentary behaviour. These findings suggest that intervention designers should more explicitly consider the home environment when aiming to reduce student sedentary behaviour and should seek to reduce sitting in a way that promotes, or at least does not interfere with, productivity.